2010
DOI: 10.1108/17568691011089891
|View full text |Cite
|
Sign up to set email alerts
|

Do concerns about climate change lead to distress?

Abstract: Purpose -Climate change news and educational awareness programs have swamped Australia in the past four years, with earlier campaigns raising awareness in Europe and the USA via television and the internet. What is the impact on people's psychological states of such concerns? The purpose of this paper is to explore the psychological impact of climate change within the general population and investigate what makes an individual vulnerable to distress. Design/methodology/approach -A questionnaire was completed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
198
2
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(225 citation statements)
references
References 32 publications
18
198
2
7
Order By: Relevance
“…Even though there are some prior studies supporting the link between worry about global environmental problems and low well-being, they are all cross-sectional [61][62][63]. An alternative explanation could be that worry about climate change to some extent is a sub-type of a general tendency to experience anxious and depressive feelings in everyday life, as sometimes seems to be the case with nuclear worry (see [64,65]).…”
Section: Problem-focused Copingmentioning
confidence: 96%
“…Even though there are some prior studies supporting the link between worry about global environmental problems and low well-being, they are all cross-sectional [61][62][63]. An alternative explanation could be that worry about climate change to some extent is a sub-type of a general tendency to experience anxious and depressive feelings in everyday life, as sometimes seems to be the case with nuclear worry (see [64,65]).…”
Section: Problem-focused Copingmentioning
confidence: 96%
“…Climate-related impacts also cause emotional and psychological distress to many people, especially to those who are vulnerable [19,20]. By the same token, studies have reported that people are concerned about the impacts of climate change [21]. However, studies also show that individuals distinguish between the effects of climate change on their personal lives and on society.…”
Section: Introductionmentioning
confidence: 99%
“…Two other studies considered the influence of pre鈥恊xisting mental illness. People with high levels of anxiety were susceptible to distress resulting from concerns about climate change (Searle and Gow, ). In contrast, pre鈥恊xisting mental health issues were not significantly associated with post鈥恡raumatic distress disorder among children following a cyclone disaster (McDermott et al ., ).…”
Section: Resultsmentioning
confidence: 99%